Variability among 2D and 3D methods of calculating mitral valve area: a comparative study with pressure half time method - Agarwal, Amit Kumar; Sharma, Deewakar; Baidya, Sajan Gopal; Prajapati, Dipanker (Nepalese Heart Journal, 2017)
Background and Aims: The aim of this study was to evaluate the feasibility, reproducibility and accuracy of Live Three dimensional Echocardiography (3DE), Two dimensional Echocardiography (2DE) and Three dimensional Xplane Echocardiography (3D Xplane) for the estimation of mitral valve area (MVA) and to assess which method has the best agreement with the MVA non- invasively evaluated by the Pressure half time (PHT) method in isolated rheumatic mitral valve stenosis (RMVS). Methods: In 40 patients with isolated RVMS in sinus rhythm (29 female) MVA was determined by Doppler PHT method and compared with measurements obtained by 2DE, Live 3DE and 3D Xplane method. All measurements were performed by two independent observers. Results: For both observers mean MVA was calculated minimum with 3DE (observer 1: 0.68±0.19, observer 2: 0.68±0.19 ). Intraobserver variability was least with 3D Xplane method (observer 1 cv 0.23 , observer 2 cv 0.23). Although there was no significant interobserver variability for each method, it was least for MVA by 3D Xplane method (difference -0.036) and maximum for 3DE method (-0.098) . Difference of each method with PHT showed lowest difference with 3D Xplane (-0.30) and highest with 3DE (-0.63). Conclusions: TTE 3D Xplane provides accurate and highly reproducible measurements of MVA and can easily be performed from optimal PLAX view and corresponding parasternal short-axis views acquired in the same bisected image using 3D Xplane technique . It was much easier and faster to define the image plane in short axis with the smallest orifice area when 3D Xplane method was used. Nepalese Heart Journal 2017; Vol 14(2), 13-17DOI